Analysis on trending electromagnetic exposure levels at homes and proximity next to base stations along three years in a city - Çerezci, Osman; Kanberoğlu, Baha; Yener, Şuayb Çağrı (Journal of Environmental Engineering and Landscape Management, 2015)
Electromagnetic field exposure levels of people living in the closest houses to the GSM transmitting antennas were investigated in a city between 2010 and 2012. At the end of 3-year period, trend of the electromagnetic exposure levels was determined especially for indoor/outdoor environments near the base station antennas. Because of increasing number of base stations by years and changing of the technology, it is determined that average electromagnetic exposure values in the city increased in a certain extent each year. Total and frequency selective measurements were performed in indoor/outdoor places. The results were compared by International ICNIRP limits. In addition, possibility of the compliance with some European countries which have applied low limit values are discussed to minimize involuntary exposure to electromagnetic fields at indoor/outdoor environments. Consequently, a suggestion is made and discussed for obtaining relatively homogeneous distribution of electromagnetic field exposure at indoor/outdoor environments near base station antennas to eliminate extent values.